Aborsi Menurut Moral Katolik dalam Terang Ensiklik Evangelium Vitae - Eugenius Ervan Sardono (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2020)
The main focus of this article is to parse abortion in light of Catholic morals. The church authorities base their teachings in the encyclical, as one of these Catholic moral teachings is contained in the evangelium vitae. Abortion is a social phenomenon that has existed for a long time and is a hot topic of conversation. Abortion is divided into two, namely provocative and spontaneous abortion. In this study, the authors focused on the review of provocate abortion. The purpose of this article is (1) to elaborate on the reality of abortion in light of the Encyclical Evangelium Vitae, (2) How does the Encyclical Evangelium Vitae reinforce the concept of life and (3) What does the Catholic Church teach about abortion and its contribution to the world of health? This paper analyzes the abortion phenomenon with the text interpretation method, a phenomenological study of qualitative studies. Based on what is found, that the Catholic Church has a great concern with issues that violate the right to life. So, it can be concluded that, for whatever reason the Catholic Church still rejects abortion.